The Trade-Off Theory of Capital Structure in Emerging African Economies: A Review and Empirical Analysis - Jules KOUNOUWEWA; Deng CHAO (African Scientific Journal, 2024)
Abstract This article provides an in-depth review and empirical analysis of the Trade-Off Theory of capital structure within the context of emerging African economies. The Trade-Off Theory posits that firms balance the tax benefits of debt against the costs of financial distress when determining their optimal capital structure. While this theory is well-established in developed markets, its applicability in the unique economic and financial environments of African countries remains underexplored. This study aims to fill that gap by examining the determinants of capital structure decisions among firms in selected African economies, considering both macroeconomic and firm-specific factors. The research employs a mixed-method approach, combining a comprehensive literature review with quantitative data analysis. Data is collected from financial statements and macroeconomic indicators across several African markets. Regression models are utilized to identify the primary factors influencing capital structure decisions, such as profitability, firm size, growth opportunities, and market conditions. The findings reveal that, while the Trade-Off Theory provides a useful framework, the capital structure in emerging African economies is significantly influenced by factors unique to the region, including political risk, exchange rate volatility, and access to credit. These results offer new insights into the capital structure behavior of firms in Africa and underscore the need for tailored financial strategies that consider both global theories and local contexts. The study also highlights important policy implications for regulators and corporate managers in developing sustainable financial frameworks that can support economic growth and development. Future research is recommended to explore more granular data and include other emerging markets for comparative analysis. Keywords: Trade-Off Theory; Capital Structure; Emerging Economies; African Markets; Empirical Analysis. Résumé Cet article propose une analyse empirique et une analyse approfondie de la théorie du compromis de la structure du capital dans le contexte des économies africaines émergentes. La théorie du compromis postule que les entreprises équilibrent les avantages fiscaux de la dette par rapport aux coûts de la détresse financière lorsqu'elles déterminent leur structure de capital optimale. Bien que cette théorie soit bien établie sur les marchés développés, son applicabilité dans les environnements économiques et financiers uniques des pays africains reste sous-explorée. Cette étude vise à combler cette lacune en examinant les déterminants des décisions de structure du capital parmi les entreprises de certaines économies africaines, en tenant compte à la fois des facteurs macroéconomiques et des facteurs spécifiques à l'entreprise. La recherche utilise une approche mixte, combinant une revue complète de la littérature avec une analyse quantitative des données. Les données sont collectées à partir d'états financiers et d'indicateurs macroéconomiques sur plusieurs marchés africains. Des modèles de régression sont utilisés pour identifier les principaux facteurs influençant les décisions de structure du capital, tels que la rentabilité, la taille de l'entreprise, les opportunités de croissance et les conditions du marché. Les résultats révèlent que, bien que la théorie des compromis offre un cadre utile, la structure du capital dans les économies africaines émergentes est fortement influencée par des facteurs propres à la région, notamment le risque politique, la volatilité des taux de change et l'accès au crédit. Ces résultats offrent de nouvelles perspectives sur le comportement de la structure du capital des entreprises en Afrique et soulignent la nécessité de stratégies financières adaptées qui tiennent compte à la fois des théories mondiales et des contextes locaux. L'étude met également en évidence d'importantes implications politiques pour les régulateurs et les gestionnaires d'entreprise dans l'élaboration de cadres financiers durables qui peuvent soutenir la croissance économique et le développement. Des recherches futures sont recommandées pour explorer des données plus granulaires et inclure d'autres marchés émergents pour une analyse comparative. Mots-clés : théorie des compromis ; structure du capital ; économies émergentes ; marchés africains ; analyse empirique.